2020
DOI: 10.1002/spe.2830
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary and time based bug‐assignment: A recommender system for open‐source projects

Abstract: SummaryBug‐assignment (BA), the task of ranking developers in terms of the relevance of their expertise to fix a new bug report is time consuming, which is why substantial attention has been paid to developing methods for automating it. In this article, we describe a new BA approach that relies on two key intuitions. Similar to traditional BA methods, our method constructs the expertise profile of project developers, based on the textual elements of the bugs they have fixed in the past; unlike traditional meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…It is used to emphasize specific keywords and de-emphasize the common terms, and shown to work well on textual data. 16,17,41,44,45,99 Tf-idf gives an ''overlap score'' 79 to a document regarding the query. Having several documents (developer profiles), the document with the highest score is considered the document most similar (and most relevant as a response) to the given query (bug report).…”
Section: Experiments Setup and Data Setmentioning
confidence: 99%
“…It is used to emphasize specific keywords and de-emphasize the common terms, and shown to work well on textual data. 16,17,41,44,45,99 Tf-idf gives an ''overlap score'' 79 to a document regarding the query. Having several documents (developer profiles), the document with the highest score is considered the document most similar (and most relevant as a response) to the given query (bug report).…”
Section: Experiments Setup and Data Setmentioning
confidence: 99%
“…We use our previous method [17], VTBA, as the baseline method –since it was the latest text‐based IR model for BA and outperformed previous state‐of‐the‐art approaches. We further revise it to handle multiple sources of expertise and show that the improvement is non‐trivial.…”
Section: Background and Related Researchmentioning
confidence: 99%
“…In a recent research [17], we proposed a method called VTBA which is based on original TF‐IDF [18, 27–29] and showed that it outperforms many other recent approaches. It only considers the technical keywords (the ones that are a Stack Overflow tag) and disregards others.…”
Section: Bug Assignment Based On Multiple Sources Of Evidence Of Thmentioning
confidence: 99%
See 2 more Smart Citations